Polymer sandwich laminates for improved impact resistance - Tan, Elissa Shimin. (2013)
The main objective of this project is to study the effect of the number of layers of honeycomb material on the low-velocity impact response of sandwich structures. The thickness of the overall composite specimens is kept relatively constant, with similar number of prepreg plies and similar overall thickness of honeycomb core layers. Epoxy GFRP prepregs and Nomex aramid honeycomb cores of thicknesses 2 mm, 4 mm and 12 mm are used. The different impact responses of the sandwich structures are analysed using experimental investigation as well as finite element simulation with the engineering simulation software ANSYS. The experiment results showed that the one-layer honeycomb core structure performed significantly better than the multi-layer honeycomb core structures. The finite element simulation method could not support the experimental findings due to the oversimplified model used, but was useful in providing insight into the gross behaviour of the sandwich laminates.